Teachers’ perceptions on the availability and utilization of assistive technology for pupils with learning disabilities in Eti-Osa, Lagos State - Dimiri, Eunice; Sunday, Eniola Michael (Utan Kayu Publishing, 2025)
Assistive technology (AT) plays a crucial role in inclusive education by enhancing learning opportunities for pupils with learning disabilities and promoting their full participation in academic activities. This study investigated teachers’ perceptions of the availability and utilization of assistive technology in primary schools in Eti-Osa Local Government Area, Lagos State, Nigeria. Using an ex post facto descriptive research design, 191 teachers from public and private schools were selected through purposive sampling. Data were collected using a validated questionnaire, the Assistive Technology in the Classroom (ATC), with a reliability coefficient of 0.87. The findings revealed that although several types of assistive technologies were available, they were insufficient to meet the learning needs of pupils with disabilities. Computers and iPads were the most commonly available and utilized tools, while specialized devices such as speech synthesizers, graphic organizers, and speech-to-text converters were notably absent. More than half of the teachers agreed that assistive technology enhances pupils' learning outcomes by compensating for cognitive deficits, thereby fostering classroom independence and task completion. However, barriers such as inadequate funding, lack of teacher training, and limited stakeholder commitment hinder the optimal use of these technologies. Addressing these challenges requires concerted efforts from government bodies, non-governmental organizations, and educational institutions. This study contributes to the growing body of literature on assistive technology in inclusive education and emphasizes the need for improved resource allocation and teacher training to bridge the educational gap for pupils with learning disabilities.